2022
DOI: 10.1088/1361-6579/ac8f12
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble classification combining ResNet and handcrafted features with three-steps training

Abstract: Objective This work presents an ECG classificator for variable leads as a contribution to the PhysioNet/CinC Challenge 2021. It aims to integrate deep and classic machine learning features into a single model, exploring the proper structure and training procedure. Approach From the initial 88253 signals, only 84210 were included. Low quality and unscored recordings were excluded. Three different database subsets of 40365 recording each were created by dividing in three normal sinus rhythm and sinus bradycardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Garcia et al [77] integrated a deep branch composed of a modified ResNet with dilated convolutional layers and squeeze and excitation block, concatenated with a wide branch that integrated 20 cardiac rhythm features into a fully connected 3-layered network. Similarly, a model based on the ResNet architecture with a multi-head attention mechanism demonstrated that the multi-head attention layer might not significantly impact the final classification performance [78] .…”
Section: Ai Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%
“…Garcia et al [77] integrated a deep branch composed of a modified ResNet with dilated convolutional layers and squeeze and excitation block, concatenated with a wide branch that integrated 20 cardiac rhythm features into a fully connected 3-layered network. Similarly, a model based on the ResNet architecture with a multi-head attention mechanism demonstrated that the multi-head attention layer might not significantly impact the final classification performance [78] .…”
Section: Ai Models For Ecg Cardiac Rhythm Classificationmentioning
confidence: 99%